PENGARUH PARTISIPASI ANGGARAN, INFORMASI ASIMETRIS, PENEKANAN ANGGARAN DAN KOMITMEN ORGANISASI PADA SENJANGAN ANGGARAN - Dewi, Nyoman Purmita; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
Normal 0 false false false IN X-NONE X-NONE The purpose of this study was to find out the effect of (1) budgetary participation on the budgetary slack, (2) asymmetric information on budgetary slack, (3) budget emphasis on budgetary slack and (4) organizational commitment on budgetary slack. The sample in this study is the boss and the staff involved in the budgeting process at the Regional Enterprise Parking Denpasar obtained by the method of census or in other words using saturated samples. The data was collected using the instrument in the form of interviews and questionnaires. The hypothesis tested in this study by using analysis of multiple linear regression. The results of this study are (1) there is a negative effect between budgetary participation and budgetary slack (2) there is a positive effect between asymmetric information and budgetary slack (3) there is a positive effect between budget emphasis and budgetary slack, and (4) there is a negative influence between organizational commitment and budgetary slack. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: budgetary; information; and commitment